Patient perception towards clinicians before and after treatment at U.P. College of Dentistry School year 1996-1997 - Santos, Manolet B.
This study is about what patients perceived of certain clinician variables which are: knowledge of dental procedures; clinical skills possessed; attitude towards the patients; materials and equipment being used; and patient management skills. Ninety six respondents answered survey questionnaires upon arrival for their first dental appointment. This survey (labelled Survey A) contained ratings of patient expectations of the clinicians. One hundred and one respondents answered survey questionnaires on patient reactions after completion of dental treatment (labelled Suvey B). Regardless of demographic variables, the patient consensus revealed high expectations of the clinicians. Results of the second survey showed many differences in patient perceptions regarding the same variables after treatment. 83% of the respondents indicated satisfaction to the treatment received while 81% of the respondents mentioned plans of recommending U.P.C.D. service.